Development of an application for accessing and analyzing RDPLF data - Benoit Thieurmel; Martin Masson (RDPLF, 2020)
The collection of information in the database of a medical registry finds its first interest in the possibility for a doctor and a care team to analyze their results and to compare themselves with other teams for the purpose of sharing experience and knowledge. Since 1986, the French Language Peritoneal Dialysis Registry (RDPLF) has collected data from 45,000 patients with renal failure treated at home in French-speaking countries. A partnership has been created between the RDPLF and Datastorm (https://www.datastorm.fr), the expertise and consultancy subsidiary of the ENSAE-ENSAI Group (National Schools of Economics and Statistics) in order to develop an application that allows to carry out simple statistical queries on the RDPLF database, by means of a user-friendly WEB interface. Thus, any doctor or member of the healthcare team can evaluate, without any special statistical skills, results by region and by French-speaking country. Special access also allows any center to compare its own results with those of a reference region. The generated graphics can be used for presentations during team meetings or for work. The application is based on the R software (https://www.r-project.org) and its SHINY visualization interface (https://shiny.rstudio.com). We report on development modalities and its functionalities (based on preselected criteria: incidence rate, prevalence, survival, infection rate, distribution of treatments, nursing aspects). This article describes how both nurses and doctors can easily realize studies with the application. Its bilingual interface also opens it up to English-speaking communities and thus facilitates international communication.